Influence of drying method on drying kinetics and qualities of longan fruit leather - Somkiat Jaturonglumlert (2018)
© 2015 by Maejo University, San Sai, Chiang Mai, 50290 Thailand. The effects of some drying techniques (hot-air drying, far-infrared drying and microwave-vacuum drying) on the qualities of longan fruit leather, as well as on the drying rate, specific energy consumption, and other properties of longan fruit leather were studied. The drying time for microwave vacuum drying was shortest and the specific energy consumption was also lowest. However, far-infrared drying gave products with the best qualities. It also reduced the drying time and specific energy consumption in comparison to hot-air drying and was found to be suitable for the production of longan fruit leather.